(untitled) (Prithvi Academic Journal, 2026)
This research study examined the long-run causal relationship between human development and economic growth in Nepal using annual time-series data from 1990 to 2024. The Autoregressive Distributed Lag (ARDL) bounds testing approach was applied, and it demonstrated a cointegrated and statistically significant relationship between the Human Development Index (HDI) and GDP growth. The empirical results suggest that in the long run, an increase in the HDI by 0.01 is associated with an increase in GDP growth of 2.035 percentage points. The structural break analysis shows that both the Gorkha earthquake in 2015 (–1.62 percentage points) and the COVID-19 pandemic in 2020 (–2.20 percentage points) had large and statistically significant negative effects at the 5% level. The error correction term (ECT = –0.39, p < 0.05) shows that deviations from the long-run equilibrium are corrected at a rate of 39% per annum. Diagnostic tests confirm model stability, the absence of serial correlation residual serial homoscedasticity, and residual normality. The findings suggest that prioritizing inclusive education and sustainable income growth is essential for improving human development and achieving resilient long-term economic growth in Nepal. The study further recommends continued investments in inclusive education and equitable income growth to strengthen Nepal’s capacity to withstand external shocks.